Beyond Seattle: WATS and Advanced Imaging in Barrett's Esophagus. Issue 1 (March 2021) - Anandasabapathy, Sharmila; Mansour, Nabil M.
Barrett's esophagus is the sole known precursor for esophageal adenocarcinoma. Endoscopic surveillance for Barrett's esophagus is recommended to help identify and manage dysplasia, with the ultimate goal being prevention or early detection of esophageal adenocarcinoma. The current standard of care for endoscopic surveillance for Barrett's esophagus, the Seattle protocol, has many drawbacks. Methods to overcome these disadvantages have been an active area of research. This review will focus on some of the technologies to help improve dysplasia surveillance in Barrett's esophagus, including advanced endoscopic imaging, artificial intelligence, and wide-area transepithelial sampling with computer-assisted 3D analysis (WATS-3D).